Qualidade de vida relacionada à saúde dos pais/responsáveis por crianças/adolescentes em tratamento para leucemia ou linfoma - Isabel Zanforlin Freitas (2022)
Throughout the years, pediatric cancer has evolved from a fatal disease to a chronic health condition with life threat. The reduction in the disease’s mortality rate is due to the continuous advances in the field of medicine and the efficiency of available treatments. The most prevalent types of children’s cancer are leukemia and lymphoma, each require until 3 years of chemotherapy varying in intensity throughout different phases. The lengthy treatment can be wearing to the patient and their families, considering the number of medical appointments, hospitalizations, and symptoms: adverse from the medication, and from the disease itself. To evaluate the impact that the aggravating factors can have on the patient’s and related families’ Health-Related Quality of Live (HRQoL) research focused on self-report is required. As so this study’s objective is to identify the psychosocial impact that leukemia/lymphoma and its treatment in children/adolescents can cause in the parents/guardians and family’s lives. A cross-sectional study was conducted with a non-probability sample of 52 families with children/adolescents under treatment for leukemia or lymphoma at a reference hospital in Belo Horizonte, Brazil. The parents/guardians answered questions about their socioeconomical and demographical status and questions related to the disease, and its treatments. The Brazilian version of PedsQL™ Family Impact Module was also used to measure the possible impact of leukemia and lymphoma on the HRQoL of families. The descriptive data analysis, bivariate logistics regression, and multiple logistics regression was made with the SPSS software (IC 95%, p<0,05). In most of the studied subjects the mother was the main guardian of the patient (78.8%), the monthly income of 51.9% of the families was 1 minimum wage salary and 65,4% shared their home with up to 4 people. From the children/adolescents 88,5% were being treated for leukemia and 42,3% were female. The multiple analysis that when the mother was the person responsible for the patient there was a chance 13,9 times higher of a greater negative impact to the HRQoL when compared to when the guardian was a different person (OR=13,89; 95%IC: 1,39-138,92; p=0,025). Other independent variables where not associated with the impact on the HRQoL of families. Considering the parents/guardians proxy-report on the parental function, the biggest negative impact was related to worry (mean=46,2; SD±25,56). The family function domains “Daily Activities” and “Family Relationships” had means of 64,4 (SD±36,60) and 84,4 (SD±25,25) respectively, exhibiting a greater impairment in the daily activities than in relationships. It is concluded that childhood cancer and its treatment affect the family’s HRQoL. When the mother is primarily responsible for the child/adolescent with cancer, she is more likely to perceive the negative impact that the disease and its treatment can bring to the family nucleus.